2013
DOI: 10.1093/mp/sst067
|View full text |Cite
|
Sign up to set email alerts
|

Rice Male Development under Drought Stress: Phenotypic Changes and Stage-Dependent Transcriptomic Reprogramming

Abstract: Drought affects rice reproduction and results in severe yield loss. The developmental defects and changes of gene regulation network in reproductive tissues under drought stress are largely unknown. In this study, rice plants subjected to reproductive stage drought stress were examined for floral development and transcriptomic changes. The results showed that male fertility was dramatically affected, with differing pollen viability in flowers of the same panicle due to aberrant anther development under water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 90 publications
6
106
0
3
Order By: Relevance
“…Inflorescences of wild-type and mutant plants were collected and fixed in FAA (formaldehyde-acetic acid-ethanol) solution and embedded in Technovit 7100 resin (Heraeus Kulzer) as described (Jin et al, 2013). Semithin sections were prepared by cutting inflorescence materials into 1-mm-thick sections using a motorized RM2265 rotary microtome (Leica Microsystems) and then were stained with 0.05% Toluidine Blue O for 15 to 30 min and photographed by bright-field microscopy.…”
Section: Light and Electron Microscopy Observationmentioning
confidence: 99%
“…Inflorescences of wild-type and mutant plants were collected and fixed in FAA (formaldehyde-acetic acid-ethanol) solution and embedded in Technovit 7100 resin (Heraeus Kulzer) as described (Jin et al, 2013). Semithin sections were prepared by cutting inflorescence materials into 1-mm-thick sections using a motorized RM2265 rotary microtome (Leica Microsystems) and then were stained with 0.05% Toluidine Blue O for 15 to 30 min and photographed by bright-field microscopy.…”
Section: Light and Electron Microscopy Observationmentioning
confidence: 99%
“…Twenty-eight rice meiotic genes have been characterized to date (Luo et al, 2014), and more than 300 meiosis stage-specific genes have been identified in rice anthers (Fujita et al, 2010;Jin et al, 2013). Here, our main focus was on differentially down-regulated meiosis-related or stage-specific genes associated with the IPE factor.…”
Section: Polyploidy Enhanced Epistatic Interactions Between Pollen Stmentioning
confidence: 99%
“…The complexity of gene expression during anther and ovary development has been revealed using microarrays or RNA sequencing in diploid rice (Tang et al, 2010;Aya et al, 2011;Deveshwar et al, 2011;Jin et al, 2013;Pan et al, 2014), maize (Zea mays; DukowicSchulze et al, 2014), wheat (Triticum aestivum; Crismani et al, 2006), and Arabidopsis (Arabidopsis thaliana; Twell, 2003, 2004;Yang et al, 2011;Zhao et al, 2014). Microarrays have been used to identify differentially expressed genes in autotetraploid plants.…”
mentioning
confidence: 99%
“…A coincidência do estresse hídrico com a meiose das células dos grãos de pólen é o principal fator para esterilidade das espiguetas (Jin et al, 2013).…”
Section: Resultsunclassified
“…Em plantas sob essa condição, há aumento da resistência difusiva ao vapor de água mediante o fechamento dos estômatos, o que reduz a transpiração e o suprimento de CO 2 , além de diminuir o crescimento celular e aumentar a fotorrespiração (Shinozaki & Yamaguchi-Shinozaki, 2007). Esses efeitos resultam em perda de vigor, diminuição na altura da planta, aumento na esterilidade do grão de pólen e redução na produtividade (Jongdee et al, 2006;Jagadish et al, 2007;Jin et al, 2013).…”
Section: Introductionunclassified